O cinema de Ray Harryhausen: efeitos especiais e maneirismo no cinema de Hollywood // The films of Ray Harryhausen: special effects and mannerism in Hollywood cinema - Carrega, Jorge Manuel (Contemporanea, 2016)
Através de uma análise histórico-formal, este trabalho propõe uma leitura maneirista da obra de Ray Harryhausen (1920-2013), um dos maiores criadores de efeitos especiais do cinema de Hollywood, verdadeiro autor de uma série de filmes que se distinguem pelo uso virtuoso da técnica, colocada ao serviço de narrativas fantásticas, construídas numa clara referencia a grandes clássicos do cinema de Hollywood. ABSTRACT Through a historical and formal analysis, this paper proposes a Mannerist reading of the work of Ray Harryhausen (1920-2013), one of Hollywood’s most acclaimed creators of special effects, the true author of a series of films that are recognaisable by a virtuoso use of technique in fantastic narratives, developed in clear reference to some great Hollywood classic films.